Reformists' thought on the Sunna (a comparative study on Moenawwar Chalil's and Fazlur Rahman's principles of the Sunna) - Muhammad Julkarnain (Fak. Ushuluddin, Studi Islam dan Pemikiran Agama UIN SUKA, 2011)
why, 1